Sistem Informasi Akademik Berbasis Web Pada Sekolah Menengah Atas (SMA) Negeri 20 Kabupaten Tangerang - Santoso, Tri; Sulaeman, Dicky (Fakultas Teknologi Informasi Institut Teknologi Adhi Tama Surabaya, 2021)
At present the development of technology has been increasingly rapid, especially in terms of information using technology. Not a few who take advantage of opportunities from current technological developments. Many systems and applications are made to help and facilitate an activity. Likewise with the service system and school facilities that also take advantage of current technological developments, namely website-based academic information systems that aim to facilitate students, teachers and parents in monitoring and getting information about teaching and learning activities quickly, anywhere and anytime. A website-based academic information system that can be accessed anywhere can facilitate and be an appropriate alternative for finding and delivering information about academics effectively. SMA Negeri 20 Kab. Tangerang is one of the schools that does not have an academic information system where the data processing is still using conventional methods. The existence of an academic information system means that the school has the right alternative media as a provider of information, so that it can make it easier for teachers, students and parents to deliver and get information on grades, subjects, study schedules and other information. The system development model used to design and build this application is the waterfall model. And this academic information system is designed and developed using the programming languages PHP, HTML, CSS using the Mysql Database.